2019
DOI: 10.1016/j.rmcr.2019.01.005
|View full text |Cite
|
Sign up to set email alerts
|

ARDS from miliary tuberculosis successfully treated with ECMO

Abstract: Tuberculosis is a rare cause of acute respiratory distress syndrome (ARDS) and mortality rates are high in tuberculosis patients that need treatment with mechanical ventilation. Experience of the use of extracorporeal membrane oxygenation (ECMO) in such circumstances is scarce. We report the case of an 18 year old man where prolonged therapy (50 days) with extracorporeal membrane oxygenation (ECMO) allowed extensive lung damage from miliary tuberculosis to heal. The case reflects how challenging the diagnosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…For the mother, miliary TB may cause multiple organ involvement, such as liver dysfunction and bone marrow TB, as well as ARDS [ 22 ], for which ECMO has proven to be an effective treatment [ 24 ]. The disease may also have a far-reaching impact on the foetus, such as a higher risk of miscarriage and preterm delivery, intrauterine growth retardation and stillbirth, and congenital TB [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…For the mother, miliary TB may cause multiple organ involvement, such as liver dysfunction and bone marrow TB, as well as ARDS [ 22 ], for which ECMO has proven to be an effective treatment [ 24 ]. The disease may also have a far-reaching impact on the foetus, such as a higher risk of miscarriage and preterm delivery, intrauterine growth retardation and stillbirth, and congenital TB [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous case report indicated that high-dose steroid therapy for pulmonary TB contributed to a decreased requirement for long-term steroid use [7]. However, evidence for the effect of corticosteroids on ARDS due to disseminated TB is still lacking [15]. Any pharmacotherapy used in the present case did not appear to contribute to the rapid improvement.…”
Section: Discussionmentioning
confidence: 57%
“…Previous reports on successful treatment of VV-ECMO in TB-induced ARDS focused on prolonged use [[6], [7], [8],14]. The duration of use of VV-ECMO in previous studies was 36 [6], 52 [7], and 89 [8,15] days. In the recent report, a patient with miliary TB-induced ARDS on ECMO therapy without ventilator weaned from ECMO after 50 days [13].…”
Section: Discussionmentioning
confidence: 99%
“…The evidence of ECMO support in these cases is scarce and is only in the form of case reports. However, the experience had been positive, with 11/12 cases with good results [ 2 , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , 17 , 18 ], with the non-recovered patient being a case where TB was diagnosed post mortem [ 16 ]. Most of these cases used VV-ECMO, with VA-ECMO reserved for concomitant cardiologic involvement [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, ECMO has been used as therapy for ARDS due to TB. However, published evidence is scarce, with only 12 cases published to our knowledge [ 2 , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] ]. We present a case of a patient with ARDS secondary to TB in whom ECMO was used as a salvage therapy in the middle of SARS-CoV-2 pandemic.…”
Section: Introductionmentioning
confidence: 99%